(3EOGQI GdJShjb GdMOjKs - (3Ydj adGM(B, (3GdRZHjs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2015)
(3jVe GdJShjb CSSg h eaGgjeg, eONd Gdi EOGQI GdfTGW GdJShjbj, GSJQGJjLjI EOGQI GdfTGW GdJShjbj, YedjI GdJNWjW GdJShjbj, YedjI GdJfXje GdJShjbj, YedjI GdJfSjb GdJShjbj, YedjI GdJhLjg GdJShjbj, YedjI GJNGP GdbQGQGJ GdJShjbjI, YedjI GdQbGHI GdJShjbjI, eONd Gdi JShjb GdNOeGJ, GdJShjb GdOhdj, GdJShjb GdGdcJQhfj aj efXeGJ GdCYeGd(B.s
Keywords: (3COGQI GdeHjYGJs; (3EOGQI GdCYeGds; (3GdJShjbs; (3JcfhdhLjG(B- (3GdJShjbs